A clinical and mechanistic study of topical borneol‐induced analgesia - Shu Wang; Dan Zhang; Jinsheng Hu; Qi Jia; Wei Xu; Deyuan Su; Hualing Song; Zhichun Xu; Jianmin Cui; Ming Zhou; Jian Yang; Jianru Xiao (EMBO Molecular Medicine)
Abstract Bingpian is a time‐honored herb in traditional Chinese medicine (TCM). It is an almost pure chemical with a chemical composition of (+)‐borneol and has been historically used as a topical analgesic for millennia. However, the clinical efficacy of topical borneol lacks stringent evidence‐based clinical studies and verifiable scientific mechanism. We examined the analgesic efficacy of topical borneol in a randomized, double‐blind, placebo‐controlled clinical study involving 122 patients with postoperative pain. Topical application of borneol led to significantly greater pain relief than placebo did. Using mouse models of pain, we identified the TRPM8 channel as a molecular target of borneol and showed that topical borneol‐induced analgesia was almost exclusively mediated by TRPM8, and involved a downstream glutamatergic mechanism in the spinal cord. Investigation of the actions of topical borneol and menthol revealed mechanistic differences between borneol‐ and menthol‐induced analgesia and indicated that borneol exhibits advantages over menthol as a topical analgesic. Our work demonstrates that borneol, which is currently approved by the US FDA to be used only as a flavoring substance or adjuvant in food, is an effective topical pain reliever in humans and reveals a key part of the molecular mechanism underlying its analgesic effect.